Disruption of gastric barrier function by luminal nitrosative stress: a potential chemical insult to the human gastro-oesophageal junction. Issue 3 (26th October 2007) - Ara, N; Iijima, K; Asanuma, K; Yoshitake, J; Ohara, S; Shimosegawa, T; Yoshimura, T
Abstract : Objective: The human gastro-oesophageal junction is exposed to abundant amounts of luminal reactive nitrogen oxide species (RNOS) derived from the enterosalivary re-circulation of dietary nitrate. The aim of this study is to investigate the direct effects of luminal RNOS on the adjacent gastric barrier function using an ex vivo chamber model. Methods: A chamber model in which the rat gastric mucosal membrane was mounted between the two halves of a chamber was designed to simulate the microenvironment of the lumen and the adjacent mucosa of the gastro-oesophageal junction. On the mucosal side of the chamber, RNOS were generated by the acidification of physiological concentrations of sodium nitrite. The epithelial barrier function was evaluated by electrophysiological transmembrane resistance, and membrane permeability with [3 H]mannitol flux. The expression of occludin was evaluated by immunohistochemistry and immunoblotting. Dinitrosyl dithiolato iron complex (DNIC) was also measured by means of electron paramagnetic resonance spectroscopy to confirm the diffusion of RNOS from the mucosal lumen into the mounted mucosa. Results: The administration of acidified nitrite to the mucosal lumen caused both a decrease in transmembrane resistance and an increase in epithelial permeability, suggesting a disturbance of the gastric barrier function. These changes were accompanied by a derangement of the expression of occludin. The diffusion of luminal RNOS into the mounted membrane was confirmed by showing the generation of DNIC within the tissue. Conclusions: Simulating the microenvironment of the human gastro-oesophageal junction, this study demonstrated that RNOS generated luminally at the human gastro-oesophageal junction can derange the barrier function of the adjacent tissue by disrupting the tight junction.